Experimental androgen deficiency and associated structural changes in the muscle tissue of the external anal sphincter - A. S. Pronina; G. N. Suvorova; N. N. Vologdina (Сеченовский вестник)
Aim. We aimed to study the histological and ultramicroscopic structure of the striated muscle tissue of the external  anal sphincter (EAS) of mature male rats under experimental androgen deficiency.Materials and methods. The study included 10 male laboratory rats aged 8 months, which were randomly divided  into 2 groups of 5 each. The experimental group underwent bilateral orchiectomy to create testosterone deficiency.  After 45 days, rats were sacrificed. We studied the concentration of testosterone in histological sections of EASs  using light microscopy and ultramicroscopy. We also determined the diameter of muscle fibers and the thickness  of endomysium, the area of muscle fibers, connective tissue, myofibrils and cytoplasm, identification of glycogen  granules in the cytoplasm and intermyofibrillar space, as well as changes in mitochondria. Results. In the experimental group, on the 45th day after surgical castration, the testosterone level was 2.5 times  lower than in the control group 2.69 (2.52; 2.73) nmol/l vs. 7.20 (6.83; 7.21) nmol/l, p = 0.008. Using morphometric  analysis, we found that in the experimental group after surgical castration the diameter of the muscle fibers was  statistically significantly smaller than in the control group: 6.56 (3.96; 7.24) µm vs. 9.52 (8.88; 10.44) µm, p < 0.001,  while the thickness of the endomysium in the experimental group was greater: 3.34 (3.11; 3.78) µm vs. 1.62 (1.51;  1.86) µm, p < 0.0001. The ratio of muscle fiber area/connective tissue area was statistically significantly lower in the  group after castration: 1.64 (1.50; 1.78) vs. 4.00 (3.17; 5.25), p < 0.0001. The ratio of myofibril area/cytoplasmic area  changed in the experimental group towards the predominance of cytoplasm 0.79 (0.67; 0.79) vs. 5.25 (5.25; 7.33),  p < 0.0001. With an increase in cytoplasmic volume, an increase in the number of glycogen granules was observed;  pathological forms of mitochondria were identified: swelling, destruction of cristae and vacuolization of their matrix. Conclusion. Under conditions of testosterone deficiency, along with atrophic processes, compensatory and adaptive  mechanisms are formed in the striated skeletal muscle tissue of the EAS, aimed at restoring its metabolic and  functional organization